THE COMPARISON OF POTASSIUM IODATE CONCENTRATION IN JANGKA SALT OF MATANG GLUMPANG DUA PRODUCTION FROM THE COOKING AND NATURAL DRYING PROCESS BY IODOMETRI METHOD - Ernita Silviana; Fauziah Fauziah; Azmalina Adriani (Lantanida Journal, 2019)
The need for salt at this time is very high, especially in the food sector, so analytes that are declared very good for health must meet the requirements of the KIO3 compound (potassium iodate), SNI requirements are 30-80 ppm. The purpose of this study was to compare the levels of potassium iodate in term salt with two processes, namely cooking and natural drying. The sample used comes from the term salt produced in Matang Glumpang Dua. The method used in this research is iodometry. The results showed that the average levels of potassium iodate in cooked salt amounted to 32.13 mg/kg and dried salt content amounted to 50.32 mg/kg, with a ratio of levels of 18.19 mg/kg. From the results of the analysis of the two salts meet the requirements specified by SNI 01-3556-2010.